Students' Self-Esteem at School: The Risk, the Challenge, and the Cure - Prihadi Kususanto; Melissa Chua (Journal of Education and Learning (EduLearn), 2012)
As one of the most important elements in students’ psychological well-being, self-esteem is often neglected at school. In schools where students are grouped based on their academic abilities (Between Class Ability Grouping or BCAG, or tracking), teachers are likely to have different expectancies toward different group of students; towards high-achieving students, they tend to be academically supportive, while towards low-achieving students, they tend to control students’ behavior in order to avoid disciplinary problems. In turn, students observe their teachers’ classroom behavior and develop different perception towards their teachers’ expectancy. Eventually, self-esteem of the students is affected by their perceived teachers’ expectancy (PTE), where the effect is not always positive. In other words, while most teachers would rather not to teach in mixed classrooms, the practice of BCAG might contribute negative effect to students’ self-esteem. Therefore, any strategy to improve students’ self-esteem might not be able to produce long-lasting result, because teachers’ expectancy towards the students is strongly influenced by the classroom segregation. However, it was discovered recently that Locus of Control (LoC) mediates the effect of PTE on students’ self-esteem. In the light of that, there is a hope to develop or maintain students’ self-esteem levels by developing some strategies based on Behavior Modification Theories to alter students’ LoC.